Environmental Technologies to Treat Selenium Pollution 2021
DOI: 10.2166/9781789061055_0101
|View full text |Cite
|
Sign up to set email alerts
|

Microbial reduction of selenium oxyanions: energy-yielding and detoxification reactions

Abstract: Selenium (Se), a semi-metallic chemical element in the oxygen group (group 16 [VIa]) of the periodic table, can be beneficialeven essential in some instancesfor microbes and animals, including humans, when present at a suitable concentration, whereas no essential Se requirement has been shown for higher plants (Lenz & Lens, 2009;Winkel et al., 2015). Se is an essential trace element required for the biosynthesis of seleno-amino acids such as selenocysteine (Se-Cys) (Bock et al., 1991;Gromer et al., 2005) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
1
0
0
Order By: Relevance
“…have been reported in the last years to efficiently reduce Se oxyanions (Faramarzi et al, 2020 ; Herrero & Wellinger, 2015 ; Hussein et al, 2022 ; Liang et al, 2019 ). The molecular mechanisms proposed to be involved in the metabolic reduction pathway of inorganic Se to Se 0 are very similar to those reported for bacteria (Herrero & Wellinger, 2015 ; Lampis & Vallini, 2021 ). Interestingly, rhizosphere fungi isolated from Se‐resistant plants in polluted sites are not inhibited in the presence of this element (Shoeibi et al, 2017 ).…”
Section: Biological Synthesis Of Sesupporting
confidence: 79%
“…have been reported in the last years to efficiently reduce Se oxyanions (Faramarzi et al, 2020 ; Herrero & Wellinger, 2015 ; Hussein et al, 2022 ; Liang et al, 2019 ). The molecular mechanisms proposed to be involved in the metabolic reduction pathway of inorganic Se to Se 0 are very similar to those reported for bacteria (Herrero & Wellinger, 2015 ; Lampis & Vallini, 2021 ). Interestingly, rhizosphere fungi isolated from Se‐resistant plants in polluted sites are not inhibited in the presence of this element (Shoeibi et al, 2017 ).…”
Section: Biological Synthesis Of Sesupporting
confidence: 79%
“…These gene expression changes indicated that 200 mg/kg selenite had no negative effects on G. lucidum JNUSE-200, and it was not necessary to activate the expression of these genes to overcome adversity. G. lucidum CGMCC 5.26 needed to activate the high expression of these genes to transform selenite to a lower valence state of Se, reducing its toxic effect ( Supplementary Figure S2 ) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%